2012
DOI: 10.1021/ja211649a
|View full text |Cite
|
Sign up to set email alerts
|

Intermolecular Hydroacylation: High Activity Rhodium Catalysts Containing Small-Bite-Angle Diphosphine Ligands

Abstract: Readily prepared and bench-stable rhodium complexes containing methylene bridged diphosphine ligands, viz. [Rh(C(6)H(5)F)(R(2)PCH(2)PR'(2))][BAr(F)(4)] (R, R' = (t)Bu or Cy; Ar(F) = C(6)H(3)-3,5-(CF(3))(2)), are shown to be practical and very efficient precatalysts for the intermolecular hydroacylation of a wide variety of unactivated alkenes and alkynes with β-S-substituted aldehydes. Intermediate acyl hydride complexes [Rh((t)Bu(2)PCH(2)P(t)Bu(2))H{κ(2)(S,C)-SMe(C(6)H(4)CO)}(L)](+) (L = acetone, MeCN, [NCCH(… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

12
95
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 130 publications
(107 citation statements)
references
References 69 publications
12
95
0
Order By: Relevance
“…The amount of catalyst needed can be dramatically reduced if two separate catalysts are employed, each of which have been optimised for the individual steps of the process. We have previously shown that complex D (featuring the small bite‐angle di( t Bu)phosphine) can catalyse the hydroacylation of unactivated alkenes at as low as 0.1 % catalyst loading 15. The most efficient catalyst for the aryl sulfide reduction step is complex E ,17 which can efficiently deliver the reduced compound by using only 0.5 mol % loading (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of catalyst needed can be dramatically reduced if two separate catalysts are employed, each of which have been optimised for the individual steps of the process. We have previously shown that complex D (featuring the small bite‐angle di( t Bu)phosphine) can catalyse the hydroacylation of unactivated alkenes at as low as 0.1 % catalyst loading 15. The most efficient catalyst for the aryl sulfide reduction step is complex E ,17 which can efficiently deliver the reduced compound by using only 0.5 mol % loading (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…Both compounds 7 and 8 are essentially inactive in catalysis, showing that once formed they represent a deactivation pathway for this process in CH 2 Cl 2 (or C 2 H 4 Cl 2 ). An active species is formed upon addition of 3 a to [Rh(Cy 2 PCH 2 PCy 2 )(MeCN) 2 ][BAr F 4 ] ( 9 )15 to form [Rh(Cy 2 PCH 2 PCy 2 )(SMe){σ,κ‐C 6 H 4 (OCMe)}(NCMe)][BAr F 4 ] ( 10 ), rather than the dimer. This reaction is rapid suggesting that dissociation of fluorobenzene is the limiting factor in the reaction of C with 3 a in CH 2 Cl 2 .…”
Section: Resultsmentioning
confidence: 99%
“…That no branched final product is observed suggests a higher barrier to reductive elimination from the corresponding intermediate, as noted previously. [8, 13b] H/D exchange was observed into free 4 a during catalysis, suggesting reversible aldehyde and alkene binding. The measured KIE is similar to other systems in which reductive elimination is proposed to be turnover-limiting,[8b, 13] rather than irreversible C–H activation (KIE ≈2.5[7c, 18]), and is likely an equilibrium isotope effect.…”
mentioning
confidence: 98%
“…We first demonstrated that employing this new catalyst allowed reduced catalyst loadings for substrates previously reported. [13b] For example, using complex 1 a catalyst loading of 5 mol % and 80 °C were required for the hydroacylation of methyl methacrylate with a yield of 68 %; however, when catalyst 3 a was employed, we were able to not only decrease the loading and the temperature but also significantly increase the yield (entry 1). A similar improvement was observed in the case of N -methyl maleimide (entry 2).…”
mentioning
confidence: 99%
“…We and others have shown cationic rhodium(I) complexes ligated by small bite‐angle diphosphine and η‐FC 6 H 5 to be effective pre‐catalysts for intermolecular hydroacylation . However, the substrate scope is limited to aldehydes or alkenes containing a β‐coordinating group . When on the aldehyde, this motif drives the pre‐equilibrium of aldehyde binding by chelation effect and also blocks a vacant site on the corresponding acyl hydride complex that comes from C−H activation.…”
Section: Resultsmentioning
confidence: 99%